Japanese Conversation Learning through 'Active Learning' for Yafsi Volunteers in Medan : Pembelajaran Percakapan Bahasa Jepang Melalui Active Learning Bagi Relawan Yafsi di Medan - Mhd. Pujiono; Budi Agustono; Murniati Br. Barus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Community service activities 'Basic Japanese Language Conversation Learning (Nihongo no Kaiwa) through active learning for Yayasan Fajar Sejahtera Indonesia (YAFSI) volunteers in Medan' is an appropriate activity in improving the foreign language qualifications of volunteers who are active in the community. YAFSI is a foundation engaged in the field of community empowerment, specifically women's empowerment and child protection in Medan. In this service, the team in collaboration with the YAFSI has held Japanese language conversation training with active learning methods for one month. The active learning method is proven able to facilitate the emergence of life skills. This learning leads to optimizing the intellectual and emotional involvement of students in the learning process, directed to learn students to learn to obtain and process the acquisition of learning through knowledge, skills, attitudes and values. The lecture and Q&A method is also used to provide knowledge and theories about the basics of Japanese. After the training was conducted, the community service team also provided assistance with Japanese learning literature materials. The development of YAFSI volunteers in community service activities is reportedly written and published in the mass media.